Role of the serotonin receptor type 7 (5-HT7) in autoimmune disease - Nußbaumer, Mia (Jihočeská univerzita, 2023)
Serotonin receptor type 7 (5-HT7) displays immunomodulatory functions and is overexpressed in individuals with Crohn's disease. Here, we set out to determine 5-HT7 mode of interaction with its cognate proteins Gs and G12. A unique type of coupling, termed 'inverse coupling' is known to occur between the 5-HT7 receptor and the Gs protein. The aim of our research was to determine whether G12 can also undergo this kind of coupling. We found that the G12 protein has a surprisingly lower mobility than Gs implying a specific interaction with a membrane domain or another membrane-localized protein. For both G proteins, we were unable to detect their inverse coupling with the 5-HT7 receptor at room temperature. Our findings indicate peculiar differences in G protein mobility and emphasize the importance of temperature for studies of interactions between G proteins and G protein-coupled receptors.
Role of the serotonin receptor type 7 (5-HT7) in autoimmune disease
Keywords: G-protein; G protein-coupled receptor; cell signaling; serotonin; microscopy; single-molecule imaging; inflammation; G-protein; G protein-coupled receptor; cell signaling; serotonin; microscopy; single-molecule imaging; inflammation